Rapid and Quantitative Cyclization of Multiple Peptide Loops onto Synthetic Scaffolds for Structural Mimicry of Protein Surfaces - Timmerman, Peter; Beld, Joris; Puijk, Wouter C; Meloen, Rob H (Chembiochem : a European journal of chemical biology, 2005)
No need for side‐chain protection in the cyclization reaction of cysteine‐containing linear peptides onto bromomethylated aromatic scaffolds (see scheme). The reaction is extremely fast and clean and runs to completion in less than 15 min at room temperature.